Overexpression of BDNF increases excitability of the lumbar spinal network and leads to robust early locomotor recovery in completely spinalized rats. - Ewelina Ziemlińska; Sebastian Kügler; Melitta Schachner; Iwona Wewiór; Julita Czarkowska-Bauch; Małgorzata Skup (PLoS ONE, 2014)
Strategies to induce recovery from lesions of the spinal cord have not fully resulted in clinical applications. This is a consequence of a number of impediments that axons encounter when trying to regrow beyond the lesion site, and that intraspinal rearrangements are subjected to. In the present study we evaluated (1) the possibility to improve locomotor recovery after complete transection of the spinal cord by means of an adeno-associated (AAV) viral vector expressing the neurotrophin brain-derived neurotrophic factor (BDNF) in lumbar spinal neurons caudal to the lesion site and (2) how the spinal cord transection and BDNF treatment affected neurotransmission in the segments caudal to the lesion site. BDNF overexpression resulted in clear increases in expression levels of molecules involved in glutamatergic (VGluT2) and GABAergic (GABA, GAD65, GAD67) neurotransmission in parallel with a reduction of the potassium-chloride co-transporter (KCC2) which contributes to an inhibitory neurotransmission. BDNF treated animals showed significant improvements in assisted locomotor performance, and performed locomotor movements with body weight support and plantar foot placement on a moving treadmill. These positive effects of BDNF local overexpression were detectable as early as two weeks after spinal cord transection and viral vector application and lasted for at least 7 weeks. Gradually increasing frequencies of clonic movements at the end of the experiment attenuated the quality of treadmill walking. These data indicate that BDNF has the potential to enhance the functionality of isolated lumbar circuits, but also that BDNF levels have to be tightly controlled to prevent hyperexcitability.